Perlindungan Hukum terhadap Kurir Jika Terjadi Ketidaksesuaian Pengiriman Barang terhadap Konsumen dalam Transaksi Cash on Delivery (COD) - Arifuddin Muda Harahap; Dimas Ari Syahputra; Dini Rizki Marshanda; Fhitrysya Hariyanti; M. Akbar Hanafi Lubis; Rahmad Daffa (Universitas Batanghari Jambi, 2023)
This study aims to find out how legal protection is for couriers in online buying and selling activities, especially in the COD payment system, and to find out the legal protection that can be given to couriers who get strict action from buyers because of non-conformance of ordered goods especially legal protection for couriers against buyers who default and refuse the goods they ordered. The method used in this study is a normative juridical method by examining library materials or secondary data sources, namely laws and regulations, books, and legal studies. Based on these methods, the research was conducted using a statutory approach and a case approach. The results of the study show that the courier's duties in the online shopping COD system are as a deposit recipient, as a person who replaces the goods delivery service company in carrying out the power of attorney from the seller, and as a recipient of payment from the buyer. The legal protection that can be given to couriers in the online shopping COD system is to guarantee that the courier is not responsible for non-conformance or damage to goods that are not caused by his mistakes or negligence.